2015
DOI: 10.5039/agraria.v10i1a5133
|View full text |Cite
|
Sign up to set email alerts
|

Seleção de marcadores ISSR e diversidade genética em uma população de Elaeis guineensis

Abstract: Resumo: O objetivo deste trabalho foi selecionar primers ISSR para serem utilizados em futuras análises de diversidade genética em populações naturais de P. reticulata. Amostras foliares de cinco indivíduos da espécie foram coletadas para extração e purificação de DNA. O DNA obtido das amostras foi submetido a ensaios de PCR utilizando 28 primers, seguida de eletroforese em gel de agarose para análise dos fragmentos amplificados. Foram selecionados 10 primers por possuírem número considerado de locos e boa def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 13 publications
2
12
1
5
Order By: Relevance
“…As a management strategy, these results may support the implementation of subsidies for the genetic conservation of the species in extractive communities. Chagas et al (2015) have suggested that the reduction of the population size of Elaeis guineensis Jacq. (Arecaceae) is due to a loss of habitat and increased agricultural activities at the study site.…”
Section: Genetic Bottlenecksmentioning
confidence: 99%
See 1 more Smart Citation
“…As a management strategy, these results may support the implementation of subsidies for the genetic conservation of the species in extractive communities. Chagas et al (2015) have suggested that the reduction of the population size of Elaeis guineensis Jacq. (Arecaceae) is due to a loss of habitat and increased agricultural activities at the study site.…”
Section: Genetic Bottlenecksmentioning
confidence: 99%
“…As such, molecular markers are fundamental in analyzing patterns of SGS, characterizing natural plant populations, and estimating gene diversity, inbreeding, gene flow, and degree of kinship (Vieira and Carvalho, 2008;Gonçalves et al, 2010). Of the molecular markers available, ISSR (inter-simple sequence repeat) markers are commonly used in population genetic studies due to their ease of handling, the production of significant polymorphism, short turnaround time for results, and lower cost when compared to other markers Chagas et al, 2015). As such, several studies have used ISSR markers to evaluate the SGS of plant populations (Melo Júnior et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Devido à herança dominante, a presença do fragmento (banda) pode representar o homozigoto dominante ou o heterozigoto, enquanto a ausência pode ser infligida o estado homozigoto recessivo, à ocorrência de inserções/deleções, ou à adição ou perda de um sítio de reconhecimento do primer (Zietkiewicz et al, 1994). Apesar do uso contínuo de marcadores ISSR (Brandão et al, 2011;Duarte et al, 2015;Melo Junior et al, 2015), ainda são escassos os estudos envolvendo a metodologia de seleção e indicação do número mínimo de locos para uso na genética de populações (Chagas et al, 2015;Fajardo et al, 2014;Mendonça et al, 2013).…”
Section: Introductionunclassified
“…Em análises de diversidade genética de Hancornia speciosa Gomes, foram utilizados seis primers, gerando 63 locos e apenas 30 (47,62%) apresentaram polimorfismo (Costa et al, 2015). Em estudos moleculares com Elaeis guineensis, Chagas et al (2015) também selecionaram seis primers, onde encontraram um total de 68 locos, sendo 34 polimórficos.…”
Section: /6unclassified